Communication Audit: Analysing Communication Effectiveness Through Organisation Communication Evaluation (OCE) - Emmanuel, Vincent Gerrard; Salsabila, Alya Dwi; Listiani, Diva; Adjie, Marcellino; Siallagan, Yepta (Komunika : Jurnal Ilmiah Komunikasi, 2025)
The objective of this study is to identify and analyse the communication issues currently being experienced, and to provide concrete recommendations for addressing these issues through communication audits in the Keluarga Pelajar dan Mahasiswa Cirebon Daerah Istimewa Yogyakarta (KPC-DIY) in the Special Region of Yogyakarta. The qualitative research method was employed, utilising a descriptive approach. The findings of this study indicate that KPC-DIY is experiencing communication issues, particularly a lack of interaction on the Instagram account @kpc.diy and a decline in participation from new members. This has resulted in ineffectiveness in the organisation's programmes. Consequently, it is recommended that a communication audit be conducted. The study also presents several recommendations, including the use of alternative posting formats, the incorporation of interactive captions, and the development of programmes aligned with the interests of students to enhance the involvement of new members.